Autologous activated platelet‐rich plasma in hair growth: A pilot study in male androgenetic alopecia with in vitro bioactivity investigation. (2nd December 2020) - Zhou, Yinghui; Liu, Qingmei; Bai, Yanshuang; Yang, Kai; Ye, Yaqi; Wu, Kejia; Huang, Junhong; Zhang, Yue; Zhang, Xuewenjun; Thianthanyakij, Traidit; Wang, Ji'an; Zhu, Yifei; et al.
Abstract: Background: Platelet‐rich plasma (PRP) is effective in the treatment of androgenetic alopecia (AGA). Aims: The purpose of this study is to assess the effect of PRP on the proliferation of human follicle dermal papilla cells (HFDPCs), to observe the effect of PRP on the growth of hair follicles and hair shaft in vitro, to measure growth factors, and to evaluate the efficacy and safety of PRP injection. Patients/Methods: The effect of PRP on the proliferation of HFDPCs was observed. The length of hair follicle and hair shaft in vitro was measured. Then, the concentration of growth factors (EGF, FGF‐2, FGF‐7, IGF‐1, HGF, PDGF‐BB, and VEGF‐A) was evaluated. Half‐head injection of PRP was conducted to 10 males. Three treatments were conducted at 30‐day intervals. Digital photographs were taken; hair diameter, hair density, unit density of hair follicles, and terminal hair/ vellus hair were analyzed. Results: Platelet‐rich plasma significantly promoted the proliferation of HFDPCs. Under the PRP culture, the hair follicle and hair shaft were grown, and the hair growth length on the 3rd and 6th days was greater than that of the control. PRP contained growth factors such as EGF, FGF‐2, FGF‐7, IGF‐1, HGF, PDGF‐B, and VEGF‐A. Hair diameter, hair density, and unit hair follicle density on the PRP injection side peaked in the 6th month. The terminal hair/ vellus hair of the PRP injection side reached a peak in the 4th month. The average patient satisfaction during the entire treatment was 5.4 points (0‐10 points). Conclusion: Platelet‐rich plasma can promote hair growth. PRP injection is safe and effective for the treatment of AGA.